INFLUENCE OF THE NATIONAL-CULTURAL ENVIRONMENT ON THE FORMATION OF ECOLOGICAL CULTURE IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS OF THE REPUBLIC OF KARAKALPAKSTAN - Xusnetdinov Ulugbek Imametdinovich (Bright Mind Publishing, 2025)
The peculiarities of the national-cultural environment play a key role in the formation of ecological culture among students of higher educational institutions of the Republic of Karakalpakstan. The study analyzes the interrelationship of Karakalpak national traditions, attitude towards nature, and ecological consciousness. The results show the positive influence of the national environment on the development of ecological culture.
Keywords: National values, ecological culture, national-cultural environment, self-awareness, ecological education, integration in education, traditional knowledge, cultural identity, interdisciplinary approach, collective experience.